Living alone, loneliness, and depressive symptoms among Indonesian older women. Issue 9 (16th October 2020) - Widhowati, Siwi Sri; Chen, Ching-Min; Chang, Ling-Hui; Lee, Chia-Kuei; Fetzer, Susan
Abstract: In this study, the researchers aimed to investigate the factors associated with loneliness and depressive symptoms among Indonesian older women. A secondary data analysis of the Indonesian Family Life Survey-5 was conducted. Data from 1233 women aged 60 years or above were analyzed using logistic regression. Results indicated fewer than one in five older women lived alone, half reported loneliness, and 16% reported depressive symptoms. Living alone was significantly associated with loneliness and depressive symptoms. Different factors were associated with loneliness and depressive symptoms. Loneliness and depression were found to be independent constructs of older women living alone in Indonesia.